Wczesnośredniowieczny skarb monet z Jordanowa, gm. Świebodzin - Tabaka, Arkadiusz (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2024)
During rescue excavations carried out in 2008 in Jordanowo, Świebodzin commune, Lubuskie voivodeship, on site 7 (on the route of the planned S3 expressway), a treasure was discovered of early medieval coins loosely scattered on an area of approx. 2 m². It lay directly under the humus layer, about 40 cm deep, between the graves of an early medieval cemetery, which probably was in operation since the 2nd half of the 11th century for at least 100 years. The article presents a detailed description of the coins, including, but not limited to metrological data, production marks, traces of use, a breakdown by type and variety and references to similar finds. The discovered collection included both entire coins and pieces thereof. Prominent among them were 2 denarii of Ethelred II, 2 German denarii from the mints in Bardowicko (preserved fragment) and Soest, and an imitation of a Magdeburg denarius, as well as cross denarii (84 whole + 15 fragments) of various types according to M. Gumowski’s Corpus Nummorum Poloniae (1939). Thus, 104 coins, including 88 whole coins and 16 fragments, were recorded in the hoard weighing 88.3 g. An analysis of the coin set has made it possible to determine the deposition to the ground at the late 11th and the early 12th century.